Evaluation of Using Radiographic Films in Measurements of Penumbra Width for Radiotherapy Applications and Stereotactic Radiosurgery: medical physics - Hegazy, Ehab A (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The accuracy of treatment field size in is a success key in cancer radiotherapy. As Increase in dose may lead to overdose side effects, and decrease in dose lead to subtherapeutic effect which increased incidence of tumor recurrence or incomplete recovery of patient. Many physical parameters should be measured very accurately in order to predict the dose distribution as physical penumbra of radiation fields. Ionization chamber is considered as slandered tools for measuring penumbra. Mega voltage x-ray energy penumbra is measured using ionization chamber due to its high accuracy in measuring absolute dose. This technique can produce the gold standard for penumbra measurements; however, it is a very time consuming and demanding process. Aim of this work is to evaluate the using radiographic films in penumbra width measurements for radiotherapy applications and stereotactic radiosurgery by comparing results obtained by standard ionization chambers to radiographic films as new tool for penumbral width measurements. Comparison between penumbra region measured by ionization chamber and o-xmat v Kodak radiographic films were carried out under the same physical and dosimeteric conditions. Penumbra width differences were found to be less than 1 mm for 6 mev, 15 mev photon beam and 6 mv, 15 mv electron beam used in radiotherapy. Measured differences were considered very small and has no effect on penumbra width measurements however o-xmat v Kodak films provide fast .easy and economic method for penumbra measurement used in radiotherapy dosimetery.